Cik Puan Pekanbaru's traditional market management strategy in dealing with the existence of a super market - Septiani Septiani (Institute of Accounting Research and Novation (IARN), 2022)
The results of this study explain that the development of the Cik Puan Pekanbaru Traditional Market faces the existence of a Super Market: Not Developing, it is caused by the position of Traditional Market Traders getting squeezed, being run over by unbalanced Business competition, where Super Market is a comfortable place to shop, while the position of Traditional Market Traders Miss Puan Pekanbaru is rundown, dirty. Cik Puan Pekanbaru's Market Management Strategy, in the form of actions that must be taken by the Managers of the Pekanbaru Cik Puan Traditional Market, so the business strategy is important so that the Cik Puan Traditional Market Trading business can survive even in the face of competition. In addition to meeting economic needs, it also reduces unemployment and poverty.